Algorithm for Computationally Efficient Imaging of Sound Speed in Conventional Ultrasound Sonography - KARWAT, Piotr (Archives of Acoustics, 2023)
The speed of sound (SoS) in tissues reflects their mechanical properties and therefore can carry valuable diagnostic information. In conventional ultrasound sonography (US), however, this information is not readily available. Furthermore, since the actual SoS is unknown, image reconstruction is carried out using an average SoS value for soft tissues. The resulting local deviations from the actual SoS lead to aberrations in US images. Methods for SoS imaging in US therefore have the potential to enable the correction of aberrations in classical US. In addition, they could also become a new US modality. There are several approaches to SoS image reconstruction. They differ in terms of input data requirements, computational complexity, imaging quality, and the potential for signal analysis at the intermediate stages of processing. This article presents an algorithm with multi-stage processing and low computational complexity. The algorithm was verified through numerical simulations and phantom measurements. The obtained results show that it can correctly estimate SoS in layered media, which in most cases model the tissue structure well. With its computational complexity of O(n), the algorithm can be implemented in real-time ultrasound imaging systems with limited hardware performance, such as portable ultrasound devices.